Isoforms of free prostate-specific antigen - Haese, A; Noldus, J; Steuber, T; Huland, H; Lilja, H (2004)
Detection of prostate-specific antigen remains the mainstay in the early detection of prostate cancer. A problem yet unsolved is the lack of specificity of this organ- but not cancer-specific marker, which generates subsequent, invasive procedures in a high number of patients without detecting prostate cancer. While the separate detection of free PSA and the ratio of free to total PSA has significantly improved specificity while maintaining high sensitivity, the number of patients undergoing unnecessary further diagnostics is still of concern. In this context, the evolving knowledge on isoforms of free PSA is a major focus of current research. Isoforms of free PSA are variants of free PSA that circulate, e.g., as precursor forms, internally cleaved variants of intact molecules, and are suggested to be either more associated with cancer or more with benign diseases. This article describes biochemical and clinical properties of the isoforms of free PSA.